An analysis of the emerging patterns of reproductive behaviour among rural women in South Africa : a case study of the Victoria East District of the Eastern Cape Province - Mfono, Zanele Ntombizanele (Stellenbosch : Stellenbosch University, 2012)
Thesis (DPhil)--Stellenbosch University, 2002.